Regulation of hepatic autophagy by stress‐sensing transcription factor CREBH. Issue 7 (26th March 2019) - Kim, Hyunbae; Williams, Dreana; Qiu, Yining; Song, Zhenfeng; Yang, Zhao; Kimler, Victoria; Goldberg, Andrew; Zhang, Ren; Yang, Zengquann; Chen, Xuequn; Wang, Li; Fang, Deyu; et al.
ABSTRACT: Autophagy, a lysosomal degradative pathway in response to nutrient limitation, plays an important regulatory role in lipid homeostasis upon energy demands. Here, we demonstrated that the endoplasmic reticulum–tethered, stress‐sensing transcription factor cAMP‐responsive element‐binding protein, hepatic‐specific (CREBH) functions as a major transcriptional regulator of hepatic autophagy and lysosomal biogenesis in response to nutritional or circadian signals. CREBH deficiency led to decreased hepatic autophagic activities and increased hepatic lipid accumulation upon starvation. Under unfed or during energy‐demanding phases of the circadian cycle, CREBH is activated to drive expression of the genes encoding the key enzymes or regulators in autophagosome formation or autophagic process, including microtubule‐associated protein IB‐light chain 3, autophagy‐related protein (ATG)7, ATG2b, and autophagosome formation Unc‐51 like kinase 1, and the genes encoding functions in lysosomal biogenesis and homeostasis. Upon nutrient starvation, CREBH regulates and interacts with peroxisome proliferator–activated receptor α (PPARα) and PPARγ coactivator 1α to synergistically drive expression of the key autophagy genes and transcription factor EB, a master regulator of lysosomal biogenesis. Furthermore, CREBH regulates rhythmic expression of the key autophagy genes in the liver in a circadian‐dependent manner. In summary, we identified CREBH as a key transcriptional regulator of hepatic autophagy and lysosomal biogenesis for the purpose of maintaining hepatic lipid homeostasis under nutritional stress or circadian oscillation.—Kim, H., Williams, D., Qiu, Y., Song, Z., Yang, Z., Kimler, V., Goldberg, A., Zhang, R., Yang, Z., Chen, X., Wang, L., Fang, D., Lin, J. D., Zhang, K. Regulation of hepatic autophagy by stress‐sensing transcription factor CREBH. FASEB J. 33, 7896–7914 (2019). www.fasebj.org